Dissipative Particle Dynamics Simulation Study on Vesicles Self‐Assembled from Amphiphilic Hyperbranched Multiarm Copolymers. Issue 8 (21st May 2014) - Wang, Yuling; Li, Bin; Jin, Haibao; Zhou, Yongfeng; Lu, Zhongyuan; Yan, Deyue
Abstract Hyperbranched multiarm copolymers (HMCs) have been shown to hold great potential as precursors in self‐assembly, and many impressive supramolecular structures have been prepared through the self‐assembly of HMCs in solution. However, theoretical studies on the corresponding self‐assembly mechanism have been greatly lagging behind. Herein, we report the self‐assembly of normal or reverse vesicles from amphiphilic HMCs by dissipative particle dynamics (DPD) simulation. The simulation disclosed both the self‐assembly mechanisms and dynamics of vesicles. It indicates that the self‐assembly of HMCs involves several steps, from randomly distributed unimolecular micelles to small spherical micelles, to membrane‐like micelles, to finally small vesicles. The membranes are formed through the direct aggregation and lateral fusion of small micelles, and the bending and closing of the membranes give rise to small vesicles. Finally, large and steady vesicles are formed through the fusion of small vesicles. In addition, the bilayer or monolayer molecular packing modes as well as the mircrophase separation behaviors of HMCs in normal or reverse vesicles have also been studied. These simulation results explore details that cannot be observed in the experiments to a certain degree, and have extended the understanding of the vesicular self‐assembly process of HMCs.